The Causality Relationship between Electricity Consumption and Economic Growth: A Case Study of Pakistan - Ali JAN; ZHAO Xin-gang; Munir AHMAD; Shahid ALI; Cem IŞIK (Communications of International Proceedings, 2020)
This paper introduces the causal associations between electricity consumption and economic growth for Pakistan based on time series of annual data from 1980 up to 2016 by utilizing Johansen Cointegration testing and Granger Causality approaches. The Johansen Cointegration Testing findings proved that the cointegrating and long-run associations exist between selected variables and empirical evidence found that the relationship between electricity consumption and economic growth exist in one-way causality direction. Renewable and nuclear energy projects should be encouraged by approving the favorable energy policies. Besides, the Pakistani government needs to establish solar energy projects for electricity generation to meet the rising energy demand in the country.
Keywords: Electricity consumption; GDP growth; Granger Causality; Pakistan